2017
DOI: 10.1002/cam4.1184
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical blood sample workup for cell‐free DNA analysis using Droplet Digital PCR for future molecular cancer diagnostics

Abstract: In current molecular cancer diagnostics, using blood samples of cancer patients for the detection of genetic alterations in plasma (cell‐free) circulating tumor DNA (ctDNA) is an emerging practice. Since ctDNA levels in blood are low, highly sensitive Droplet Digital PCR (ddPCR) can be used for detecting rare mutational targets. In order to perform ddPCR on blood samples, a standardized procedure for processing and analyzing blood samples is necessary to facilitate implementation into clinical practice. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 40 publications
4
56
0
Order By: Relevance
“…However, fluorometry can overestimate cfDNA concentration as it does not differentiate HMW DNA fragments [38]. Although previous studies have demonstrated the correlation of fluorometric quantification and real-time PCR [39,40], an electrophoresis-based instrument provides a better method considering that genomic DNA contamination is often observed after cfDNA isolation. In addition, urinary cfDNA is known to be more fragmented and variably sized compared to plasma [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, fluorometry can overestimate cfDNA concentration as it does not differentiate HMW DNA fragments [38]. Although previous studies have demonstrated the correlation of fluorometric quantification and real-time PCR [39,40], an electrophoresis-based instrument provides a better method considering that genomic DNA contamination is often observed after cfDNA isolation. In addition, urinary cfDNA is known to be more fragmented and variably sized compared to plasma [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma was thawed on ice and centrifuged at 13 000 g for 10 min prior to DNA extraction (van Ginkel et al , ). DNA was extracted from between 2.8 and 4 mL of EDTA plasma using the QIAamp® Circulating Nucleic Acid kit (Qiagen, Hilden, Germany) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Using fluorescent probes that directly bind to dsDNA, the fluorometric quantification is an approach that compensates for the disadvantage of the spectrophotometry-based methods (e.g., NanoDrop) [19]. Several previous studies have described that the fluorometric quantification is highly correlated to qPCR quantification measurements and dPCR results [20][21][22]. The fragment lengths of isolated cfDNA usually are A major limitation of this study is that the repro ducibility of each platform could not be demonstrated as we…”
Section: Discussionmentioning
confidence: 99%